(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The efficiency of commercial banks significantly impacts the stability and growth of national economies. This research explores key aspects that enhance the effectiveness of regulatory mechanisms governing the activities of commercial banks. It identifies the critical factors influencing regulatory efficiency, including legal frameworks, supervisory practices, technological advancements, and risk management strategies. The study also examines the interplay between regulatory compliance and operational performance, emphasizing the need for adaptive and dynamic regulations in the face of evolving financial markets. Using qualitative and quantitative methods, this research provides insights into best practices for fostering a resilient banking sector, offering recommendations for policymakers and regulators to optimize the regulatory environment while ensuring sustainable economic development.